Efficacy of Green Mussel Shell-Derived Hydroxyapatite as a Bone Graft Substitute in Rabbit Femoral Defects: An In Vivo Study (Open Access Indonesian Journal of Medical Reviews, 2025)
Bone grafting is a standard procedure in fracture management to enhance bone healing using osteogenic, osteoinductive, and osteoconductive materials. Bovine hydroxyapatite (HA) is a commonly used bone substitute, but its production can be expensive. Green mussel shells have emerged as a potential alternative source of HA due to their abundance and lower cost, particularly in Indonesia. This study aimed to evaluate the efficacy of HA derived from green mussel shells on bone healing in rabbit femoral defects through radiological examination. A post-test only experimental study was conducted on male New Zealand white rabbits (n=36) with surgically created femoral defects. The rabbits were randomly divided into three groups: a control group (K) with no treatment, a group (P1) treated with bovine HA, and a group (P2) treated with HA derived from green mussel shells. Bone healing was assessed radiologically at weeks 2, 4, and 6 post-surgery using the Radiographic Union Score for Tibial Fractures (RUST) score on femoral X-rays. Statistical analysis was performed to compare the RUST scores between the groups and across the different time periods, with a p-value of
Keywords: Bone graft substitutes; Femoral defect; Green mussel shell; Hydroxyapatite; Rabbit model